Impacto de las capacidades productivas para la producción de gallinas criollas, en tres comunidades rurales del distrito de Indiana, provincia de Maynas-2021 - Linares Cardenas, Mario (2022)
The theme was "Impact of the productive capacities for the production of Creole chickens, in three rural communities of the district of Indiana, province of Maynas-2021" and within it, it had as its objective: Determine the impact of: productive capacities and the Creole chicken production in rural areas of the District of Indiana. A descriptive, correlational and cross-sectional work is considered whose sample was 60 producers from the Maniti I, Indiana and Timicuro communities, (20 per community) to whom a survey was applied. In the results, according to the Likert analysis, the methods and means of technical assistance that ensure the technological adoption of chicken rearing is Good (96.7%), relating to the generation of capacities, it is also Good (71.7%); situation that shows us that both variables are related to each other. People consider the processes developed (training) as good (53.3%), related to the improvement of poultry infrastructure, food and animal health, there was participation in the design of alternative strategies for producers to carry out production (55%) and carrying out team work (55%). Social capital, which is made up of formal institutions and informal norms, attitudes, values, relationships, that manage interactions between people, as an explanatory factor of the best practices of institutions and residents and of socioeconomic development, according to Likert analysis, is considered excellent (58.3%) to good (41.7%).